Voids characteristic of hot mix asphalt containing waste cooking oil - Jaya, Ramadhansyah Putra; Masri, Khairil Azman; Ali, Mohammad Idris; Wan Azahar, Wan Nur Aifa; Ekarizan, S.; Hainin, Mohd Rosli; A. H., Norhidayah; Yaacob, Haryati (IOP Publishing, 2019)
Pure bitumen production through crude oil petroleum refining process is not desirable in road pavement application. The asphalt binder exhibits insufficient properties for pavement construction and need to be modified with various additives. In this study, the effect of untreated and treated waste cooking oil (WCO) on voids properties of hot mix asphalt was evaluated. A 5% of WCO (by weight of binder) was selected and replaced into the modified binder before being mixed with the aggregates in asphalt mixture. The voids characteristic of hot mix asphalt was determined based on Marshall Mix design test. Five different content of bitumen i.e. 4%, 4.5%, 5%, 5.5% and 6% was chosen on the basis of min and max value as required by Malaysia public work department. Test results show that the voids filled with bitumen and density was increase as the bitumen content increases from 4% to 6% for untreated and treated WCO mixes. Furthermore, the result also indicates that the void in total mix was linearly decreased when the bitumen content increased from 4% to 6%.